A refined mathematical model of physical processes in a conductor at a high-current pulse discharge - Bajda, Yevgen I.; Pantelyat, Michael G. (Харківський національний університет міського господарства імені О. М. Бекетова, 2021)
A novel mathematical model describing physical processes during the flow of an aperiodic pulse current with amplitude of 100 kA along a conductor with a circular cross-section is proposed and investigated. It is shown how a short-term electric discharge of an aperiodic shape affects the distribution of the current density in the cross-section of the conductor, causing its nonuniform heating and the appearance of significant thermal forces as well as mechanical stresses and strains. Based on the developed mathematical model, the relationship between electromagnetic, thermal and mechanical phenomena is shown, allowing a deeper understanding of the multiphysics processes taking place. The maximum values of the current density are calculated, which on the surface of the conductor reach values of 47 kA/mm2, while the temperature rise of a copper conductor with a diameter of 2.44 mm is no more than 80ºC at high temperature gradients, which causes the appearance of thermal stresses that have value (40–50)% of the value of the short-term strength limit of electrical copper. Utilization of this model allows to more accurately determine the required conductor cross-section based on the characteristics of electromagnetic, thermal and mechanical processes. It is shown that the simplified model (the condition for the uniform distribution of the current over the cross-section) gives significantly underestimated values of temperatures and does not take into account temperature deformations.

У статті запропоновано та досліджено оригінальну математичну модель, що описує фізичні процеси при протіканні імпульсного струму аперіодичної форми великої амплітуди 100 кА по круглому в перетині провіднику. Показано як короткочасний електричний розряд впливає на розподіл густини струму в поперечному перетині провідника, викликаючи його нерівномірний нагрів і появу значних термічних сил. На основі розробленої математичної моделі показано взаємозв'язок між електромагнітними, тепловими та механічними явищами, що дозволяє глибше зрозуміти мультифізичні процеси, що відбуваються. Розраховані максимальні значення густини струму, які на поверхні провідника досягають значень 47 кА/мм2, при цьому перевищення температури мідного провідника діаметром 2,44 мм становить не більше 80ºC при великих градієнтах температури, що викликає появу термічних сил, які мають значення (40–50)% від величини межі короткочасної міцності електротехнічної міді. Використання даної моделі дозволяє більш точно визначити необхідний поперечний перетин провідника та зрозуміти процеси руйнування ізоляції на підставі характеристик електромагнітних, теплових та механічних процесів. Доведено, що спрощена модель (умова рівномірного розподілу струму по перетину) дає істотно занижені значення температур, які в два рази менші, ніж максимальна температура при нерівномірній густини струму і не враховує температурні деформації.
Уточнена математична модель фізичних процесів у провіднику при сильноточному імпульсному розряді
Keywords: multiphysics processes; thermal strength; short-term electrical discharge; mathematical model; мультифізичні процеси; термічна стійкість; короткочасний електричний розряд; математична модель